Lower Platelet-to-Lymphocyte Ratio Was Associated with Poor Prognosis for Newborn Patients in NICU - Yanfei Tang; Yiqun Teng; Lingyan Xu; Guangtao Xu; Deqing Chen; Xin Jin; Wanlu Li; Xiuhui Jin; Wen Zhu; Bo Hu; Ruilin Shen; Yuzhang Zhu (Medicina, 2022)
Background: Platelet-to-lymphocyte ratio (PLR) is reported to be related to the outcome of intensive care unit (ICU) patients. However, little is known about their associations with prognosis in newborn patients in neonatal ICU (NICU). The aim of the present study was to investigate the prognostic significance of the PLR for newborn patients in the NICU. Methods: Data on newborn patients in the NICU were extracted from the Multiparameter Intelligent Monitoring in Intensive Care III (MIMIC III) database. The initial PLR value of blood examinations within 24 h was analyzed. Spearman's correlation was used to analyze the association of PLR with the length of hospital and ICU stays. The chi-square test was used to analyze the association of PLR with mortality rate. Multivariable logistic regression was used to determine whether the PLR was an independent prognostic factor of mortality. The area under the receiver operating characteristic (ROC) curve was used to assess the predictive ability of models combining PLR with other variables. Results: In total, 5240 patients were enrolled. PLR was negatively associated with length of hospital stay and ICU stay (hospital stay: ρ = −0.416, p < 0.0001; ICU stay: ρ = −0.442, p < 0.0001). PLR was significantly correlated with hospital mortality (p < 0.0001). Lower PLR was associated with higher hospital mortality (OR = 0.85, 95% CI = 0.75–0.95, p = 0.005) and 90-day mortality (OR = 0.85, 95% CI = 0.76–0.96, p = 0.010). The prognostic predictive ability of models combining PLR with other variables for hospital mortality was good (AUC for Model 1 = 0.804, 95% CI = 0.73–0.88, p < 0.0001; AUC for Model 2 = 0.964, 95% CI = 0.95–0.98, p < 0.0001). Conclusion: PLR is a novel independent risk factor for newborn patients in the NICU.